Avaliação experimental da influência da rugosidade, dureza e pressão de contato no desempenho da vedação estática metálica de gases - Pádoa, Cesar Augusto Fernandes de (2018)
This work consisted in the accomplishment of experiments to evaluate preselected factors in the performance of the static metal gas seal. Using the discipline of experiment planning, tests were designed to allow the investigation of factors such as hardness, load and roughness. The experiment consisted in monitoring the pressure drop through a metal interface with controlled surfaces. The acquisition method and selected parameters are typical of the industry, aiming to give greater familiarity of the results with day to day problems of installations and equipment. Results have been assessed through statistical tools to validate hypotheses. In addition, an investigation on the role of more descriptive factors of the surfaces than only the average measure of the heights of the asperities was conducted. A combination of descriptive parameters showed potential to increase the results of other models, since it showed a significant relationship with the pressure drop observed through the tests.